Employee Performance: The Effect of Workload and Compensation: Survey at a Restaurant in Serang, Banten - Khristina Sri Prihatin; Anggi Haerani (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aims to determine the effect of workload on employee performance at a restaurant in Serang, Banten. The effect of compensation on the performance of employees at a restaurant in Serang, Banten. The Effect of workload and compensation on the performance of employees at a restaurant in Serang, Banten. This research includes quantitative research. The population of this study were the employees at a restaurant in Serang, Banten in Serang totaling 26 people. The method used is quantitative associative. The data analysis method used T test and F test. The results showed that the results of the T test between workload and employee performance obtained Tcount > T table, namely 0.749 < t table 2.069. So the workload has no effect on employee performance. As for compensation for employee performance, it shows that the results of the T-test obtained the value of Tcount > Ttable, namely 4.058 > t table 2.069. So compensation has an effect on employee performance. F test results obtained 8.956 > f table 3.40, it can be concluded that there is an effect of workload and compensation on employee performance at a restaurant in Serang, Banten.